Gene microarray analyses of daboia russelli russelli daboiatoxin treatment of THP-1 human macrophages infected with burkholderia pseudomallei - Perumal Samy, R.; Manikandan, J.; Pachiappan, A.; Ooi, E.; Aw, L.; Stiles, B.; Franco, O.; Kandasamy, M.; Mathi, K.; Rane, G.; Siveen, K.; Arunachalam, C.; et al. (Bentham Science Publishers Ltd., 2015)
© 2015 Bentham Science Publishers. Burkholderia pseudomallei is the causative agent of melioidosis and represents a potential bioterrorism threat. In this study, the transcriptomic responses of B. pseudomallei infection of a human macrophage cell model were investigated using whole-genome microarrays. Gene expression profiles were compared between infected THP-1 human monocytic leukemia cells with or without treatment with Daboia russelli russelli daboiatoxin (DRRDbTx) or ceftazidime (antibiotic control). Microarray analyses of infected and treated cells revealed differential upregulation of various inflammatory genes such as interleukin-1 (IL-1), IL-6, tumor necrosis factor-alpha (TNF-a), cyclooxygenase (COX-2), vascular endothelial growth factor (VEGF), chemokine C-X-C motif ligand 4 (CXCL4), transcription factor p65 (NF-kB); and several genes involved in immune and stress responses, cell cycle, and lipid metabolism. Moreover, following DRR-DbTx treatment of infected cells, there was enhanced expression of the tolllike receptor 2 (TLR-2) mediated signaling pathway involved in recognition and initiation of acute inflammatory responses. Importantly, we observed that highly inflammatory cytokine gene responses were similar in infected cells exposed to DRR-DbTx or ceftazidime after 24 h. Additionally, there were increased transcripts associated with cell death by caspase activation that can promote host tissue injury. In summary, the transcriptional responses during B. pseudomallei infection of macrophages highlight a broad range of innate immune mechanisms that are activated within 24 h post-infection. These data provide insights into the transcriptomic kinetics following DRR-DbTx treatment of human macrophages infected with B. pseudomallei.